The new map of the world: The poetic philosophy of Giambattista Vico - Mazzotta, Giuseppe (New Jersey Princeton Legacy Library, 1999)
For today's readers, the great Italian philosopher of history Giambattista Vico (1668-1744) can be startlingly relevant to the social and educational divisiveness we confront at century's end: here Giuseppe Mazzotta, one of the leading Italianists in the United States, shows how much Vico, properly read, can bring to an understanding of contemporary social problems. To explore Vico's body of thought in all its monumental complexity, Mazzotta highlights the place of poetry, or "writerliness," in Vico's educational project, which links literature, history, religion, philosophy, and politics.